Unequal socioeconomic distribution of the primary care workforce: whole-population small area longitudinal study. Issue 1 (19th January 2016) - Asaria, Miqdad; Cookson, Richard; Fleetcroft, Robert; Ali, Shehzad
Abstract : Objective: To measure changes in socioeconomic inequality in the distribution of family physicians (general practitioners (GPs)) relative to need in England from 2004/2005 to 2013/2014. Design: Whole-population small area longitudinal data linkage study. Setting: England from 2004/2005 to 2013/2014. Participants: 32 482 lower layer super output areas (neighbourhoods of 1500 people on average). Main outcome measures: Slope index of inequality (SII) between the most and least deprived small areas in annual full-time equivalent GPs (FTE GPs) per 100 000 need adjusted population. Results: In 2004/2005, inequality in primary care supply as measured by the SII in FTE GPs was 4.2 (95% CI 3.1 to 5.3) GPs per 100 000. By 2013/2014, this SII had fallen to −0.7 (95% CI −2.5 to 1.1) GPs per 100 000. The number of FTE GPs per 100 000 serving the most deprived fifth of small areas increased over this period from 54.0 to 60.5, while increasing from 57.2 to 59.9 in the least deprived fifth, so that by the end of the study period there were more GPs per 100 000 need adjusted population in the most deprived areas than in the least deprived. The increase in GP supply in the most deprived fifth of neighbourhoods was larger in areas that received targeted investment for establishing new practices under the 'Equitable Access to Primary Medical Care'. Conclusions: There was a substantial reduction in socioeconomic inequality in family physician supply associated with national policy. This policy may not have completely eliminated socioeconomic inequality in family physician supply since existing need adjustment formulae do not fully capture the additional burden of multimorbidity in deprived neighbourhoods. The small area approach introduced in this study can be used routinely to monitor socioeconomic inequality of access to primary care and to indicate workforce shortages in particular neighbourhoods. http://creativecommons.org/licenses/by/4.0